Study of the potential of application of essential oils in active food packaging - Ribeiro-Santos, R. (2017)
Objective: To identify and quantify the major components of cinnamon (Cinnamomum zeylanicum L. and Cinnamomum cassia L.) and basil (Ocimum basilicum L.) (Fig. 2 and 3) EO by Ultra High Performance Liquid Chromatography coupled with Diode Array Detector (UHPLC-DAD).